(untitled) (Journal of Medical & Health Sciences Review, 2024)
Carbohydrates form one of the most multiplicity and functionally diverse categories of biomolecules that are essential in prokaryotic and eukaryotic life. Structurally they can be simple monosaccharides like glucose and fructose to extremely complicated polysaccharides like cellulose and glycogen. Their diversity is founded on the differences in the chain length, the orientation of functional groups, stereochemistry, and the type of glycosidic linkages. The functionality of such structures is predetermined by such structural characteristics as the use as a source of power, structural scaffolds or signal molecules. Structural and functional diversity of the carbohydrates will be also discussed in the paper in terms of explaining the stereochemistry of the monosaccharides, the dynamics of mutarotation and how the glycosidic links are formed in the oligo and polysaccharides. These are important processes which can be categorized as cyclization, isomeric effects, anomeric effects mentioned and explained relative to the formation of cyclic monosaccharides out of linear monosaccharides and their biological application. Special consideration is given to naturally occurring polysaccharides that consist of starch, cellulose and glycogen and the influence of the branching in their solubilities and digestibility (as well as the nature of the linkages occurring). Literature based analysis and structural diagrams in this work represent the character of carbohydrate chemistry in many areas of life that comprise nutrition, pharmacology, even materials science. The results of that sort are the basis to highlight that even minor structural variations such as the position of a hydroxyl compound can lead to notable differences in biochemical activity and utility.